Professional in Oral Tradition in Music Literature Lessons Methods of Familiarity with Samples of Music - Rustamjonova Dilkhavas Ravshvnbek qizi (Research Parks Publishing LLC, 2023)
This article discusses ways to get acquainted with examples of professional music in the oral tradition in music literature classes.